Antibiotic exposure enriches streptococci carrying resistance genes in periodontitis plaque biofilms - Zhang, Qian; Zhen, Min; Wang, Xiaochen; Zhao, FengXiang; Dong, Yang; Wang, Xiaoya; Gao, Shengtao; Wang, Jinfeng; Shi, Wenyu; Zhang, Yifei (PeerJ, 2025)
Background Periodontitis is not always satisfactorily treated with conventional scaling and root planing, and adjunctive use of antibiotics is required in clinical practice. Therefore, it is important for clinicians to understand the diversity and the antibiotic resistance of subgingival microbiota when exposed to different antibiotics. Materials and Methods In this study, subgingival plaques were collected from 10 periodontitis patients and 11 periodontally healthy volunteers, and their microbiota response to selective pressure of four antibiotics (amoxicillin, metronidazole, clindamycin, and tetracycline) were evaluated through 16S rRNA gene amplicon and metagenomic sequencing analysis. Additionally, sensitive and resistant strains were isolated and cultured in vitro for resistance evaluation. Results Cultivation of subgingival microbiota revealed the oral microbiota from periodontitis patients were more resistant to antibiotics than that of healthy. Significant differences were also observed for the microbial community between with and without antibiotics (especially amoxicillin and tetracycline) treated in periodontitis group. Conclusion Overall, after the two antibiotics (amoxicillin and tetracycline) exposed, the oral subgingival microbiota in periodontitis patients exhibited different diversity and composition. Streptococcus may account for oral biofilm-specific antibiotic resistance in periodontitis. This provides information for personalized treatment of periodontitis.
Keywords: Periodontitis; Oral microbiome; Strain isolation; Streptococcus; Antibiotic resistance